Preparation and Properties of Dialdehyde Starch Crosslinked Cellulose Nanocrystal/Tiger Nut Starch Composite Film - HE Rongjun, GAI Linlin, ZHU Zhouyi, SUN Peilong (Shipin Kexue, 2025)
To address the poor extensibility of cellulose nanocrystal (CNC)/starch composite film, tiger nut starch (TNS), dialdehyde starch (DAS), and CNC were prepared from tiger nut meal and used to fabricate CNC/TNS composite films incorporated with different concentrations of DAS. The effects of different concentrations of DAS on the structure and properties of CNC/TNS composite films were investigated. The results showed that the characteristic peak corresponding to the aldehyde group appeared at 1 730 cm-1 in the Fourier transform infrared spectroscopy (FTIR). DAS exhibited an amorphous flake-like structure with a relative aldehyde content of 85.35%. The characteristic peak for aldehyde groups disappeared in the FTIR of the composite film, accompanied by a decrease in the hydroxyl absorption peak. The X-ray diffraction (XRD) pattern showed a reduction or disappearance of the crystallization peak corresponding to CNC, indicating that DAS was crosslinked with both CNC and TNS. After crosslinking, the intermolecular interactions in the composite films were enhanced, resulting in changes in the internal molecular structure and a 21.16%–83.31% increase in elongation at break. The films with DAS concentrations of 0.2% and 1.0% showed improved compatibility between CNC and TNS, as well as reduced roughness and thickness, and the oxygen barrier capacity increased by 14.14% and 51.37%, respectively. These findings demonstrate that DAS, at an appropriate concentration, can significantly enhance the overall properties of CNC/starch composite film.